MULTITRACK RECORDING DYNAMICS IN A SOUND ENGINEER'S WORKFLOW WITH LARGE MUSICAL ENSEMBLES: PHASE COHERENCE AND ACOUSTIC ISOLATION STRATEGIES (Multidisciplinary Journal of Science and Technology, 2026)
Within the operational framework of capturing large musical ensembles, the sound engineer encounters complex acoustic phenomena, primarily microphone bleed and phase cancellation, which severely compromise the spatial integrity of multitrack recordings. The research object encompasses a prospective acoustic analysis of 45 synchronous recording sessions involving symphony orchestras and big bands at the State Conservatory of Uzbekistan between 2021 and 2025. Empirical data dictate that uncompensated acoustic spill across 24- to 64-channel arrays induces comb filtering, reducing the intelligibility of transient-heavy instruments by an average of 12.4 dB. Through objective A/B testing and algorithmic time-delay compensation routing within the Digital Audio Workstation (DAW), a deterministic protocol for phase alignment was established. Measurements indicate that applying the 3:1 distance rule in conjunction with precise spot-microphone delay adjustments (calculated via the speed of sound at 343 m/s) improved the overall phase correlation index from 0.42 to +0.88 on the standard +1/-1 phase meter scale. Practical analyses demonstrate that over-reliance on cardioid polar patterns without considering off-axis coloration leads to spectral degradation during the mixing phase. This study formulates an algorithmic methodology for spatial microphone placement and digital phase coherence optimization. The dynamics of the obtained results provide a definitive framework for reducing inter-channel crosstalk, thereby ensuring a broadcast-compliant stereophonic and immersive acoustic image for large-scale ensemble productions.